The Role of Teachers as Motivators and Facilitators in Strengthening Numeracy Literacy - Sakerani Sakerani; Andi Arifuddin Iskandar; Bambang Ismaya; St. Rahmah (Jurnal Penelitian Pendidikan IPA, 2025)
This study aims to analyze the implementation of a numeracy literacy habituation program in schools using a descriptive qualitative research method through library research. The main focus of this study is to understand various aspects that influence the success of the numeracy literacy program, including reading habituation, educational games, the provision of supporting facilities such as reading corners and educational posters, and the socialization of the program through In-House Training for teachers. Data was obtained from relevant literature sources that examine the numeracy literacy habituation program as well as best practices in its application in schools. The results of the study indicate that reading habituation and educational games can significantly improve students' literacy and numeracy skills. Additionally, strengthening teachers' capacity through continuous training is essential to ensure effective implementation. The use of supporting facilities, such as varied reading corners and informative educational posters, strengthens numeracy literacy learning outside the classroom. This study also emphasizes the important role of parents and the community in supporting the success of this program. By involving various stakeholders, it is hoped that the numeracy literacy program can be optimally implemented to enhance students' competencies in both fields.